2009
DOI: 10.1038/tpj.2009.6
|View full text |Cite
|
Sign up to set email alerts
|

Association of nicotinic acetylcholine receptor subunit α4 polymorphisms with nicotine dependence in 5500 Germans

Abstract: Polymorphisms in the CHRNA4 gene coding the nicotinic acetylcholine receptor subunit a4 have recently been suggested to play a role in the determination of smoking-related phenotypes. To examine this hypothesis, we conducted a genetic association study in three large samples from the German general population (N 1 ¼ 1412; N 2 ¼ 1855; N 3 ¼ 2294). Five singlenucleotide polymorphisms in CHRNA4 were genotyped in 5561 participants, including 2707 heavily smoking cases (regularly smoking at least 20 cigarettes per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
1
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 18 publications
10
40
1
6
Order By: Relevance
“…Subsequent studies from this research group using this cohort have gone on to reveal modest associations between CHRNA4 and adolescent nicotine dependence (Kamens et al, 2013). Similar associations between CHRNA4 and nicotine dependence have been reported in studies of adults (Feng et al 2004; Li et al, 2005; Breitling et al, 2009). Several studies have also demonstrated associations between CHRNA4 and subjective effects of nicotine (Picciotto et al, 1998; Tapper et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
“…Subsequent studies from this research group using this cohort have gone on to reveal modest associations between CHRNA4 and adolescent nicotine dependence (Kamens et al, 2013). Similar associations between CHRNA4 and nicotine dependence have been reported in studies of adults (Feng et al 2004; Li et al, 2005; Breitling et al, 2009). Several studies have also demonstrated associations between CHRNA4 and subjective effects of nicotine (Picciotto et al, 1998; Tapper et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
“…However, although this highly reproducible finding implicates this gene cluster in various aspects of nicotine dependence, whether it predicts cessation rates is unclear. For example, in both retrospective and prospective studies no evidence was found for associations of SNPs in the CHRNA5-CHRNA3-CHRNB4 gene cluster with smoking cessation (Conti et al 2008;Breitling et al 2009;Ray et al 2010). Yet, two SNPs in the CHRNA5 and CHRNB4 genes were identified as predictors of abstinence at 52-wk followup (Sarginson et al 2011), and in pharmacogenetic studies, SNPs in this gene cluster appear to predict…”
Section: Nachr Signaling-polymorphisms In Subunits and Subsequent Dowmentioning
confidence: 99%
“…For example, SNPs in CHRNA6 and CHRNB3, the genes encoding the a6 and b3 subunits, have been associated with nicotine dependence, subjective response to nicotine, and self-reported number of unsuccessful quit attempts (Bierut et al 2007;Greenbaum et al 2006;Saccone et al 2007;Zeiger et al 2008;Hoft et al 2009). Additional studies have implicated the gene encoding for the a4 subunit, CHRNA4, in various smoking phenotypes (Breitling et al 2009;Wessel et al 2010;Han et al 2011;Xie et al 2011). Furthermore, polymorphisms in the CHRNA4 gene have been significantly associated with abstinence rates while on nicotine replacement therapy (Hutchison et al 2007) or varenicline (King et al 2012), suggesting a potential role for CHRNA4 as a target for therapeutic intervention.…”
Section: Translational Research In Nicotine Dependencementioning
confidence: 99%
“…In addition, the CHRNA4 polymorphisms rs4603829 and rs4522666 were reported to modulate financial and psychological risk behaviours (Roe et al, 2009), CHRNA4 rs1044396 was associated with novelty seeking (Etter et al, 2009), whereas rs2236196, rs1044396 and rs2236196 were associated with nicotine dependence (Breitling et al, 2009). More severe consequences have some rare loss-of-function variants associated with the occurrence of amyotrophic lateral sclerosis (Sabatelli et al, 2009).…”
Section: Voltage-gated Transient Receptor Potential (Trpv) Channelsmentioning
confidence: 99%